An Inverse Association between Mediterranean- Like Dietary Pattern and Blood Pressure in Male, But Not Female, Adults in Shiraz - Farideh Dastsouz; Majid Kamali; Fatemeh Sadeghi; Sasan Amanat; Masoumeh Akhlaghi (Shiraz University of Medical Sciences, 2016)
Background: Dietary pattern is an effective way of studying the effect of diet on diseases. We investigated the association between dietary patterns and blood pressure (BP) in adults aged 20-50 years. Methods: In a cross-sectional design, 418 individuals were selected through stratified multistage random sampling from households living in different regions of Shiraz. Information on demographic characteristics, anthropometric features, dietary intakes, and systolic (SBP) and diastolic (DBP) blood pressure was gathered. Dietary patterns were determined using a validated food frequency questionnaire. Results: Three dietary patterns were specified: vegetable (high in vegetables and legumes), Western-like (high in meat, sugarsweetened beverages, salty and sweet snacks, refined grains, high-fat dairy), and Mediterranean-like (rich in low-fat dairy, fruit, vegetables, nuts, olive, fish, and low in hydrogenated fats). After adjustment for confounders, Mediterranean-like dietary pattern had an inverse association with SBP (β=-0.24; 95% CI: -5.25, -1.27) and DBP (β=-0.17; 95% CI: -3.65, -0.20) in males but not females. Vegetable and Western-like dietary patterns were not associated with BP in either sex after adjusting for confounders. Positive relationships were observed between BP and body mass index (r=0.28 and 0.33 for SBP and DBP, P<0.001), waist circumference (r=0.51 and 0.45 for SBP and DBP, P<0.001), and waist-to-hip ratio (r=0.54 and 0.44 for SBP and DBP, P<0.001). Dietary energy and carbohydrates were positively and fats inversely associated with BP. Among micronutrients, vitamin E had a significant inverse association with BP. Conclusion: Mediterranean-like dietary pattern may lower the risk of hypertension in Shiraz males.